Seronegative Maternal Ocular Myasthenia Gravis and Delayed Transient Neonatal Myasthenia Gravis - Courtney Townsel; Rebecca Keller; Kendall Johnson; Naveed Hussain; Winston A. Campbell (Thieme Medical Publishers, Inc., 2016)
Abstract Background Myasthenia gravis (MG) is an autoimmune disorder with fluctuating muscle weakness, divided into generalized and localized (ocular) forms. Maternal antibodies to acetylcholine receptors cross the placenta and may cause transient neonatal myasthenia gravis (TNMG). We present a case of seronegative maternal ocular MG and delayed TNMG. Case A 29-year-old G3P1011 underwent cesarean birth of a male infant who developed oxygen desaturation requiring supplemental oxygen on day of life (DOL) 3. Based on the clinical course and after exclusion of other diagnoses, the infant was diagnosed with TNMG. Infant's condition improved spontaneously and he was weaned off supplemental oxygen and discharged home on DOL 12. Conclusion Infants born to mothers with seronegative localized (ocular) MG are also susceptible to TNMG which may be late in onset.